A protocol for micropropagation of Aloe vera L. (Indian Aloe) – a miracle plant - DWIVEDI, N. K.; INDIRADEVI, A.; ASHA, K. I.; ASOKAN NAIR, R.; SUMA, A. (Research in Biotechnology, 2014)
Emerging axillary shoots of Aloe vera (Indian Aloe) produced new plants and roots simultaneously when cultured in MS medium supplemented with BAP 1.5 mg l-1. Each explant produced on average 14 shoots and roots simultaneously within 8 weeks. Explant multiplication could be continued even after a year by transferring each divided shoot explant to the same medium. Regenerated plantlets could be successfully transferred to the soil where they grew well within 4-6 weeks with 83% survival.